2006
DOI: 10.1126/science.1126337
|View full text |Cite
|
Sign up to set email alerts
|

Phase Modifiers Promote Efficient Production of Hydroxymethylfurfural from Fructose

Abstract: Furan derivatives obtained from renewable biomass resources have the potential to serve as substitutes for the petroleum-based building blocks that are currently used in the production of plastics and fine chemicals. We developed a process for the selective dehydration of fructose to 5-hydroxymethylfurfural (HMF) that operates at high fructose concentrations (10 to 50 weight %), achieves high yields (80% HMF selectivity at 90% fructose conversion), and delivers HMF in a separation-friendly solvent. In a two-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
1,103
1
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,532 publications
(1,138 citation statements)
references
References 24 publications
17
1,103
1
17
Order By: Relevance
“…Use of all three modifiers (DMSO, PVP, and 2-butanol) at 30 wt % fructose concentration afforded 83 % selectivity for HMF at 82 % conversion. [67] Increasing the concentration from 30 to 50 wt % decreased the HMF selectivity owing to higher rates of condensation reactions, but doubling the amount of the extracting solvent (7:3 MIBK/2-butanol mixture) increased the selectivity substantially. Experiments conducted at low fructose conversions in pure water and in the presence of 20 wt % DMSO indicated that DMSO enhances the rate of fructose conversion and decreases the rates of undesired parallel reactions.…”
Section: Reviews 7176mentioning
confidence: 97%
See 2 more Smart Citations
“…Use of all three modifiers (DMSO, PVP, and 2-butanol) at 30 wt % fructose concentration afforded 83 % selectivity for HMF at 82 % conversion. [67] Increasing the concentration from 30 to 50 wt % decreased the HMF selectivity owing to higher rates of condensation reactions, but doubling the amount of the extracting solvent (7:3 MIBK/2-butanol mixture) increased the selectivity substantially. Experiments conducted at low fructose conversions in pure water and in the presence of 20 wt % DMSO indicated that DMSO enhances the rate of fructose conversion and decreases the rates of undesired parallel reactions.…”
Section: Reviews 7176mentioning
confidence: 97%
“…[67] In a two-phase reactor system, the fructose is dehydrated in the reactive aqueous phase in the presence of HCl as acid catalyst with DMSO and/or poly(1-vinyl-2-pyrrolidinone) (PVP) added as modifiers to suppress the formation of by-products. The HMF product is continuously extracted into an organic phase (methylisobutylketone, MIBK) modified with 2-butanol to enhance partitioning from the reactive aqueous solution.…”
Section: Reviews 7176mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, fructose can be dehydrated to HMF in dilute HCl, but side reactions result in the formation of highly condensed products, which are usually called humins. [5] Dehydration of glucose to HMF is much more challenging. Unprecedented yields of HMF have been reported for chromium halides and N-heterocyclic carbene-chloride complexes in ionic liquid media.…”
Section: Introductionmentioning
confidence: 99%
“…Lewis acids are preferred because their activity is not affected by strong Brønsted acids 4. Selective dehydration of fructose to HMF can be readily achieved in the presence of Brønsted acid catalysts in biphasic organic–water solvents 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%